Gozdno in drugo rastje na levem bregu Iškega vintgarja - Accetto, Marko (Acta silvae et ligni, 2015)
Between 2004 and 2013, we studied and in 2013 also mapped the vegetation (applying the standard Central-European phytocoenological method) on the left bank of the Iški vintgar gorge (the central river basin of the Iška River, Dinaric phytogeographical region, research area 170,3 ha), which had never been studied in detail till then. On the basis of analysis of numerous analytic and synoptic tables (analyzed also by mathematical and statistical methods (Podani, 2001), the following syntaxa were identified: Primulo carniolicae-Pinetum nigrae, Fraxino orni-Pinetum nigrae var. geogr. Primula carniolica rhododendretosum hirsuti var. Laserpitium krapfii, Thymopraecocis-Pinetum nigrae s. lat., Querco-Ostryetum carpinifoliae s. lat., Carici sempervirentis-Ostryetum carpinifoliae, Omphalodo-Fagetum s. lat., Rhododendro hirsuti-Fagetum s. lat., Rhododendro hirsuti-Ostryetum s. lat., Hacquetio epipactis-Fagetum s. lat., Arunco-Fagetum s. lat., Lamio orvalae-Fagetum s. lat., Seslerio autumnalis-Fagetum s. lat., Ostryo carpinifoliae-Fagetum s. lat., Ostryo carpinifoliae-Piceetum and other nonforest communities. The majority of these syntaxa were identified even down to the lower syntaxonomic units. The results of our vegetation investigations highlight extraordinary vegetational and ecological diversity of the Iški vintgar left bank, which is without comparison in its immediate and wider vicinity.
Keywords: vegetacija; ecology; ekologija; Iški vintgar; dinarsko fitogeografsko območje; Slovenia; Slovenija